COMPETITIVENESS OF PERU IN THE NEW GLOBAL ENVIRONMENT - Gomero Gonzáles, Nicko Alberto (2013)
It is important that a country develop strong competitive to gaing solid macroeconomic result and keep constant growing. In Peru has been achieving these past years, and that have been showing in the principals indicator of economic management. The public policies implemented have created favorable scenarios to bring in investments in all productive sectors, At the same time the national companies have been develop capabilities to achieve with successes of the market globalization. The diversity of business competitions, with have develop social capabilities, technological and economics have increased to a level that have put Peru in one of the best calcification of risk free. Only through general competitiveness of all economic, socials and politics can prepare the way of growing of the country in the economics.